Ripley's believe it or not! : daily cartoons 1929-1930. - Ripley, Robert L. (Robert LeRoy), 1890-1949 (Library of American comics., 2014)
"Ripley developed 'Believe It or Not!' in the 1920s. The series took off by the end of the decade as Ripley became a world traveler, seeking stories of bizarre and unusual proportion to put in his popular newspaper cartoon feature. This book begins a chronological reprinting of Ripley's famous daily cartoons, reminding us that first and foremost Robert Ripley--explorer, radio, movie, and television personality, entrepreneur, and museum impresario--was an astounding artist and cartoonist"--Page 4 of cover.